Pensamento geométrico dos alunos do ensino médio de uma escola pública de Campo Novo do Parecis - MT - Ferreira, Kássia Anita de Freitas Rodrigues (2018)
The research aims to analyze the knowledge of Geometry of high school students of a public school of Campo Novo do Parecis -MT. The intention of the investigation is the production data, of stamp qualitative, that allow to answer the problem question: What geometric knowledge related to polygons and polyhedra do the students of the High School have? For this, as main objective we propose analyze the geometric knowledge of high school students. The problem directs the organization of the data and the choice of the referential theoretical in the work. In order to approach the history of Geometry we use Eves (1997), Rooney (2012), Piaget and Garcia (2011), Galvéz (1996), Silva; Valente (2014), Lorenzato (1995), Pavanello (1993). Regarding to the official policies and documents governing Basic Education, we based on the Basic Education Guidelines and Guidelines Law (LDB), on the current Law 13,415 / 2017, on the National Curriculum Guidelines for Basic Education (DCN) and on the Curricular Guidelines for the state of Mato Grosso, taking as clipping the guidelines for the teaching of Geometry. For the organization of the investigative questionnaires of the students, we are based on Van Hiele's theory (1957) and on the conceptions of Mathematics didactics referenced in Pais (1996, 2010, 2011). With the intent to respond to the research problem, was defined as research context an urban state school in the city of Campo Novo, Parecis-MT. We took as subjects of the research 27 students of the third year of High School and the teacher of Mathematics of the said class. As data collection instruments, we used questionnaires investigative and characterization, semi-structured interviews, field diaries. Considering the importance of choosing the axes of the analysis, organized to better read and understand the data, we opted for define them in understanding of Teacher and student about geometric thinking and geometric knowledge. From the theoretical basis and the analysis of the data it was possible to observe that the students present difficulties in the domain of the geometric concepts of polygons, and especially of the polyhedra, even in the last stage of Basic Education. We also note that the knowledge of polygons, specific content of Fundamental teaching, were not fully assimilated by the students, thus influencing the construction of new knowledge such as polyhedra, since in High School, as the official documents show, students strengthen the knowledge acquired at the previous level. Therefore, we consider that the students, when finishing the basic studies, do not present the adequate geometric knowledge and related to level three of Van Hiele